Synthesis and characterization of maghemite nanoparticles dispersed within silica matrix / Ang Bee Chin - Ang, Bee Chin (2011)
Generally, this study comprises of 3 stages. Firstly, pure maghemite nanoparticles were synthesized within 10nm size range. Secondly, the nanoparticles were encapsulated into the silica xerogel matrix to minimize agglomeration and aggregation by producing nanocomposites. Finally, the surface area of the nanocomposites was increased by modifying the matrix into silica particulate form. The nanoparticles and nanocomposites were characterized using XRD, TGA, TEM, BET, DLS and AGM. In stage I, the effects of varying the FeCl2 concentration on the properties of magnetic nanoparticles produced by Massart’s procedure were investigated. The lattice parameters of the samples obtained from XRD analysis revealed that the nanoparticles formed were maghemites (γ-Fe2O3). The magnetization curves showed no hysteresis, indicating that the particles were superparamagnetic. The crystallite, magnetic and physical sizes were similar, indicating that the particles were monocrystals. When the FeCl2 concentration increased from 0.1 to 1.0M, the size of as-synthesized maghemite nanoparticles decreased. However, when the FeCl2 concentration was increased further, the size of as-synthesized maghemite nanoparticles increased. This indicates that a very low or a very high FeCl2 concentration leads to the formation of larger particles. In addition, agglomeration and aggregation occurred for most samples. Superparamagnetic maghemite nanoparticles with the smallest size were chosen to proceed to stage II and stage III. Maghemite-silica xerogel nanocomposites were produced by dispersing the assynthesized maghemite nanoparticles into silica xerogel by sol-gel technique. The phase analysis performed using XRD confirmed that the encapsulated nanoparticles were maghemites. TEM micrographs showed that the maghemite nanoparticles were spherical and homogeneously incorporated into the silica xerogel matrix. The surface area of the nanocomposites was less than 40m2/g. This was probably due to the fact that majority of the pores in the silica gel were filled by as-synthesized maghemite nanoparticles. Reduction in average crystallite size of dispersed maghemite particles was observed after the encapsulation process compared to as-synthesized maghemite nanoparticles. However, increasing the weight ratio of Fe2O3/SiO2 in nanocomposites caused an increase in average crystallite size of embedded maghemite nanoparticles. Maghemite-silica particulate nanocomposites were prepared by a modified solgel process. The purpose of changing the matrix from xerogel to particulate form was to increase the surface area and retain its properties. It is a promising alternative technique for fabricating nanocomposites because it is simple, manufacturable, inexpensive, fast, can be prepared at room temperature and its ability to control the composition, crystalline distribution and properties of maghemite nanoparticles and nanocomposites. Moreover, no surfactant or other unnecessary precursor was involved. The HRTEM micrograph revealed that the embedded particle (core) was with the presence of atomic interspaces indicating that the particles were crystalline and covered with a noncrystalline material. The EELS result showed the presence of Fe-L3 signals, which proves that the embedded particles were iron-based compounds. In stage III, a very high surface area was attained for the produced nanocomposites (360 – 390 m2/g), compared with those of stage II. This enhances the sensitivity and the reactivity of the nanocomposites.